Generation of a localised microwave magnetic field by coherent phonons in a ferromagnetic grating - Salasyuk, A.S.; Rudkovskaya, A.V.; Danilov, A.P.; Glavin, B.A.; Kukhtaruk, S.M.; Wang, M.; Rushforth, A.W.; Nekludova, P.A.; Sokolov, S.V.; Elistratov, A.A.; Yakovlev, D.R.; Bayer, M.; et al. (American Physical Society, 2018)
A high-amplitude microwave magnetic field localized at the nanoscale is a desirable tool for various applications within the rapidly developing field of nanomagnetism. Here, we drive magnetization precession by coherent phonons in a metal ferromagnetic nanograting and generate ac-magnetic induction with extremely high amplitude (up to 10 mT) and nanometer scale localization in the grating grooves. We trigger the magnetization by a laser pulse which excites localized surface acoustic waves. The developed technique has prospective uses in several areas of research and technology, including spatially resolved access to spin states for quantum technologies.